Prenatal exposure to barium and arsenic and the odds of congenital heart defects in offspring: a nested case–control study within a birth cohort in Lanzhou, China - Dang, Yun; Sun, Jianhao; Wu, Zhenzhen; Mao, Baohong; Hang, Qinglei; Huang, Jie; Zhao, Xiaoli; Xia, Ji; Chen, Cheng; Yao, Wenxiang; Lu, Dan; Liu, Qing (Frontiers in Public Health, 2025)
BackgroundPrevious studies have identified that exposure to heavy metals increases the prevalence of congenital heart defects (CHDs); however, limited information exists regarding the association between combined exposure to barium (Ba) and arsenic (As), and CHDs. This study aims to investigate the association between prenatal exposure to Ba and As (both independently and in combination) and the risk of CHDs in offspring.MethodsIn a birth cohort study conducted in Lanzhou, China, a total of 97 mother-newborn pairs were designated as the case group, with an additional 194 pairs constituting the control group. The concentrations of Ba and As in maternal blood were quantified utilizing an inductively coupled plasma mass spectrometer. A multivariate logistic regression model was employed to examine the association between Ba and As exposure levels and the risk of neonatal CHDs and their subtypes. Interaction effects were further evaluated through the application of both additive and multiplicative models.ResultsThe concentration of As in the blood of pregnant women is positively correlated with Ba levels. Higher concentrations of maternal blood Ba level was associated with greater odds of CHDs (p = 0.008), including the isolated CHDs (p = 0.013), the multiple CHDs (p = 0.032), PDA (p = 0.014), and ASDs (p = 0.031); Similarly, higher concentrations of maternal blood As level was associated with greater odds of CHDs (p = 0.013), including the isolated CHDs (p = 0.016), the multiple CHDs (p = 0.003), PDA (p = 0.005), ASDs (p = 0.017), and AVSDs (p = 0.034). Elevated levels of barium and arsenic in maternal blood were significantly associated with increased odds of CHDs and their subtypes in offspring (All p < 0.05). Furthermore, a significant multiplicative interaction between Ba and As levels in maternal blood was identified in relation to total CHDs (p = 0.04).ConclusionExposure to Ba or As individually, as well as combined exposure to both, is significantly associated with an increased risk of CHDs in offspring.